EFEK HIPOGLIKEMIK EKSTRAK DAUN MURBEI (MORUS MULTICAULIS) TERHADAP KADAR GLUKOSA DARAH TIKUS DIABETES MELITUS - Amma, Nur Rahmi (Jurnal Sainstek, 2011)
Diabetes mellitus is one of the health problem in community. The research was aimed to analysis the hypoglycemic effect of extract Mullberry leaves in blood glucose levels diabetic rats. Completely Randomized Design was used in this research. 45 rats Sprague dawley aged 70 days were administered alloxan by intraperitonial (125 mg/kg body weight) to induced diabetes. Treatment randomly assigned to: (MKA) an extract water provided by ripe mulberry dry leaves, (MSA) an extract water provided by green mulberry fresh leaves, (MSL) an extract hexane provided by green mulberry fresh leaves, (TSA) an extract water provided by green mulberry fresh leaves, (TSL) an extract hexane provided by ripe mulberry fresh leaves, (MKL) an extract hexane provided by ripe mulberry dry leaves,(TKL) an extract hexane provided by ripe mulberry dry leaves), (TKA) an extract water provided by ripe mulberry dry leaves, and control without extract. Effect of extracts from nine treatment on blood glucose levels of diabetic rats was determined at various time interval for 1,3,5 hour after oral administration of the extract at 0,01 mg dose /g body weight rat. The results showed that the glucose levels of diabetic rats treated with extract mulberry leaves significantly decrease, respectly, at 1hour , 3 hours and 5 hours administration (p